Analysis of Genetic Algorithms for solving the 2D Orthogonal Strip Packing Problem - Glybovets, M.M.; Gulayeva, N.M.; Morozov, I.O. (Інститут програмних систем НАН України, 2018)
A class of genetic algorithms for solving the 2D Strip Packing Problem is investigated. The theoretical analysis of the complexity of implementing decoders MERA and BLF is done. Original implementations of these MERA and BLF decoders enhanced with a number of heuristic optimizations are proposed. Genetic algorithm for solving the 2D Strip Packing Problem for special cases (allowed/forbidden objects rotation by 90°) with the use of MERA/BLF decoders is proposed. Extensive computational experiments with well-known instances are performed to analyze different configurations of basic parameters of proposed genetic algorithm. The comparison of the obtained algorithm with other known algorithms is given.Problems in programming 2016; 4: 104-116